2019
DOI: 10.1038/s41598-019-56488-7
|View full text |Cite
|
Sign up to set email alerts
|

Laminin α2, α4, and α5 Chains Positively Regulate Migration and Survival of Oligodendrocyte Precursor Cells

Abstract: In the developing central nervous system (CNS), oligodendrocyte precursor cells (OPCs) migrate along blood vessels and are widely distributed in the CNS. Meanwhile, OPCs require survival factors from the extracellular microenvironment. In other tissues, laminins, heterotrimetric (αβγ) extracellular matrix proteins, promote cell migration and survival. However, the expression pattern and functions of laminins in OPC development remain poorly understood. In the present study, we first investigated the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Survival Laminin-α2 on axons Increased survival (Colognato et al, 2002) Laminin-α2 knockout Fewer OPCs and increased cell death (Relucio et al, 2012) Laminin-411 and À 511 Increased survival (Suzuki et al, 2019) Laminin-211 with PDGF Increased survival (Colognato et al, 2004;Decker, 2004;Frost et al, 1999) Laminin substrate Decreased OPC death (Hu et al, 2009) Integrin-α6β1 blockage Reduced survival (Corley et al, 2001;Frost et al, 1999) Lipid raft depletion Increased apoptosis (Decker, 2004) Integrin-α6 knockout Increased cell death (Colognato et al, 2002) Integrin-αv/α6 chimera Increased survival (Colognato et al, 2002) Integrin-β1 CKO a (CNP-Cre) Increased cell death (Benninger et al, 2006) Laminin with dystroglycan blockage No significant change (Colognato et al, 2007) Migration Laminin substrate Increased migration (Milner et al, 1996;Schmidt et al, 1997) Laminin-211 Increased migration (Frost et al, 1996) Laminin-211, À411 and À 511 Increased migration (Suzuki et al, 2019) Laminin Increased migration (Fok-Seang et al, 1995) Integrin-β1 blockage Reduced migration (Milner et al, 1996) Integrin-α6 blockage No significant change (Milner et al, 1996) Integrin…”
Section: Stimuli Effects Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Survival Laminin-α2 on axons Increased survival (Colognato et al, 2002) Laminin-α2 knockout Fewer OPCs and increased cell death (Relucio et al, 2012) Laminin-411 and À 511 Increased survival (Suzuki et al, 2019) Laminin-211 with PDGF Increased survival (Colognato et al, 2004;Decker, 2004;Frost et al, 1999) Laminin substrate Decreased OPC death (Hu et al, 2009) Integrin-α6β1 blockage Reduced survival (Corley et al, 2001;Frost et al, 1999) Lipid raft depletion Increased apoptosis (Decker, 2004) Integrin-α6 knockout Increased cell death (Colognato et al, 2002) Integrin-αv/α6 chimera Increased survival (Colognato et al, 2002) Integrin-β1 CKO a (CNP-Cre) Increased cell death (Benninger et al, 2006) Laminin with dystroglycan blockage No significant change (Colognato et al, 2007) Migration Laminin substrate Increased migration (Milner et al, 1996;Schmidt et al, 1997) Laminin-211 Increased migration (Frost et al, 1996) Laminin-211, À411 and À 511 Increased migration (Suzuki et al, 2019) Laminin Increased migration (Fok-Seang et al, 1995) Integrin-β1 blockage Reduced migration (Milner et al, 1996) Integrin-α6 blockage No significant change (Milner et al, 1996) Integrin…”
Section: Stimuli Effects Referencesmentioning
confidence: 99%
“…Consistent with this result, laminin‐α2 knockout mice have fewer OPCs and increased perinatal death of newborn OPCs at the subventricular zone (SVZ) (Relucio et al, 2012). Additionally, laminin in the basal lamina also contributes to the survival of OPCs (Suzuki et al, 2019). It has been shown that laminin‐411 and ‐511 enhance OPC survival by binding to integrin‐β1 and activating FAK, whereas laminin‐211 fails to do so (Suzuki et al, 2019).…”
Section: Laminin and Oligodendrocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wnt signaling in OPCs has critical function in this process, as it mediates association of OPCs with vessels by driving OPC expression of the chemokine receptor Cxcr4, which interacts with its ligand Sdf1 on the endothelial surface (Tsai et al., 2016). A recent study suggests that laminins expressed surrounding blood vessels positively regulate migration and survival of OPCs through the integrin β1‐FAK pathway (Suzuki et al., 2019). Vascular endothelial growth factor (VEGF‐A) secreted from cerebral endothelial cells has also been suggested to promote the migration but not the proliferation of OPCs (Hayakawa et al., 2011, 2012).…”
Section: Mechanisms Of Opc Dispersal: Engagement Of the Vasculaturementioning
confidence: 99%
“…Laminin matrices enhanced NSPC migration, expansion, differentiation into neurons and astrocytes, and elongation of neurites from NSPC-derived neurons (Liu et al, 2020), an effect possibly mediated by the α6 integrin subunit (Flanagan et al, 2006), thus confirming the importance of cellmatrix interaction in a microenvironment mimicking the NSPC niche. In addition, laminins expressed around blood vessels positively regulated the migration and survival of OPCs through the integrin β1-FAK pathway (Suzuki et al, 2019). Moreover, laminin is the most used coating for neurosphere-derived and primary OPCs (Chen et al, 2007;Lourenço et al, 2016), as the main extracellular matrix mediator of their adhesion and differentiation (Liu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%